VoIP in next generation converged networks - Toral-Cruz, Homero; Ramirez-Pacheco, Julio; Velarde-Alvarado, Pablo; Pathan, Al-Sakib Khan (CRC Press, USA, 2013)
This chapter describes the main heterogeneous networks (PSTN, SS7, ISDN, IP Network, WLAN, GSM, GPRS and UMTS) in terms of their components and services. These heterogeneous networks were designed to provide a specific service, which are initially distinct, and then converge into a single network. Voice over IP is a clear example of such convergent services, pushing towards adoption of next generation networks. In the telecommunications world, the development of technology and the enhanced services that can be offered to the end users have been captured in the concept of next generation networks. This concept does not mean a particular network but rather the evolution process of telephone networks and data networks towards a single network based on IP technology, carrying the data corresponding to multiple services offered to users (voice, video, data, etc.). On the other hand, within telecommunications, the historical separations between the heterogeneous networks have been diminishing. As a result of this fact, it is the networks convergence, where the convergent network is called, multiservice transport network.